Study Some Physiological Parameters and Association GSTM1 , GSTT1 Genes in Patients Osteoporosis in AL-Diwanya City. - AL-Khaledy, Wisam Abdan Wawi (Al-Qadisiyah Journal of Pure Science, 2017)
Several studies refer to higher levels of oxidative stress are associated with osteoporosis .The glutathione S- transferase genes have a vital role in the protection of cells from oxidative stress. The purpose of this study to know the frequency of GSTM1 and GSTT1 genes in Osteoporosis patients and asset the relationship between the genes and some physiological parameters in osteoporosis patients. Genotype (GSTM1 and GSTT1) genes were determined by polymerase chain reaction (PCR). The mean Calcium and GSH level were significantly lower (P<0.05) in osteoporosis patients compared with the control group. Show the results significantly higher (P<0.05) levels ALP, Phosphorus and MDA in osteoporosis patients compared with the control group. While don’t find significantly higher (P>0.05) GST in osteoporosis patients compared with the control group. The statistical analysis showed that the deletion in the GSTM1 (-) null genotype was increased (3.4) times in osteoporosis patients compared with control. While, the deletion in GSTT1 (-) null genotype was increased (1.5) times in osteoporosis patients. Also the results found that significant increased in the deletion in GSTM1 (-) and GSTT1 (-) (2.9) times compared with the control group.